On the Influence of Practitioners' Expertise in Component-Based Software Reviews - Goulão, Miguel; Brito e Abreu, F. (10th ECOOP Workshop on Quantitative Approaches in Object-Oriented Software Engineering (QAOOSE'2006), 2006)
Objective: To assess the influence of practitioners’ expertise in code inspection of software components. Method: Subjects expertise was determined based on their independently assessed academic record. Inspection outcome was represented by the diversity of defects found at two levels of abstraction. Results: Statistically significant correlations among expertise and inspection outcomes were found in several cases. Conclusion: The effect of expertise is observable in the inspection outcome and thus can be used in for software quality management purposes.